Labor market characteristics of the youth in Serbia and trends of labor migration in EU - Tošović-Stevanović, Aleksandra (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/006, 2022)
Youth unemployment has been an important economic and social issue over the last decades. The transition from education to work has become more difficult for young people all over Europe. As for Serbia, according to the analysis of the youth labour market, unfavourable circumstances of the post-socialist transformation in Serbia and unfavourable economic trends, as the consequence of the global economic crisis and the current pandemic crisis, have additionally aggravated the problem. Given the unfavourable position on the youth labour market, majority of young people, not only from Serbia, are seriously taking into account migration, which has played an important role in the new globalized world where the borders and restrictions on free movement of people, goods and capital have been removed. What is worrying is the fact that in Serbia, in recent decades, there has been a very high rate of migration of the population with tertiary education, which is considered to be most strongly influenced by economic and other various factors in the labour market. This situation, except for losing human resources, directly contributes to and affects the loss of the intellectual potential of the state. Therefore, the paper presents, first of all, the situation on the labour market and the position of young people in Serbia, followed by the most common motives and causes of migration of young people from Serbia into the countries of the European Union (EU).